The Promise of Aggregation-Induced Emission Luminogens for Detecting COVID-19 - Liu, Zongwei; Meng, Ting; Tang, Xiaofang; Tian, Ran; Guan, Weijiang (Frontiers in Immunology, 2021)
The long-term pandemic of coronavirus disease 2019 (COVID-19) requires sensitive and accurate diagnostic assays to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus and SARS-CoV-2 antibodies in infected individuals. Currently, RNA of SARS-CoV-2 virus is mainly detected by reverse transcription-polymerase chain reaction (RT-PCR)-based nucleic acid assays, while SARS-CoV-2 antigen and antibody are identified by immunological assays. Both nucleic acid assays and immunological assays rely on the luminescence signals of specific luminescence probes for qualitative and quantitative detection. The exploration of novel luminescence probes will play a crucial role in improving the detection sensitivity of the assays. As innate probes, aggregation-induced emission (AIE) luminogens (AIEgens) exhibit negligible luminescence in the free state but enhanced luminescence in the aggregated or restricted states. Moreover, AIEgen-based nanoparticles (AIE dots) offer efficient luminescence, good biocompatibility and water solubility, and superior photostability. Both AIEgens and AIE dots have been widely used for high-performance detection of biomolecules and small molecules, chemical/biological imaging, and medical therapeutics. In this review, the availability of AIEgens and AIE dots in nucleic acid assays and immunological assays are enumerated and discussed. By building a bridge between AIE materials and COVID-19, we hope to inspire researchers to use AIE materials as a powerful weapon against COVID-19.